2021
DOI: 10.1016/j.ajogmf.2021.100326
|View full text |Cite
|
Sign up to set email alerts
|

Effect of virtual interviewing on applicant approach to and perspective of the Maternal-Fetal Medicine Subspecialty Fellowship Match

Abstract: BACKGROUND: The 2020 application cycle for the Maternal-Fetal Medicine Specialty Fellowship Match was the first to be exclusively virtual. OBJECTIVE: Our study was designed to compare approaches and perspectives of the MFM fellowship candidates who applied with virtual interviews with those of the current Maternal-Fetal Medicine fellows, who applied with in-person interviews in 2017, 2018, or 2019. STUDY DESIGN: A survey was developed by the Society for Maternal-Fetal Medicine Fellowship Affairs Committee to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 11 publications
(8 reference statements)
0
21
0
Order By: Relevance
“…Our results supplement scant existing though expanding knowledge regarding conceptualization of virtual interview processes within OB/GYN by both applicants and interviewers. A recent study by Lewkowitz et al of Maternal-Fetal Medicine fellowship applicants suggested that OB/GYN residents are likely to accept more virtual interview offers than in-person interview offers given increased ease and convenience, which may have unintended downstream consequences on the ability of certain candidates to be offered interview opportunities [ 5 ]. Results from our study are in line with these findings, and suggest that it may be prudent to trial a system where applicants are limited in terms of number of accepted interviews to ensure that all qualified applicants are given an opportunity to interview at programs of genuine interest.…”
Section: Discussionmentioning
confidence: 99%
“…Our results supplement scant existing though expanding knowledge regarding conceptualization of virtual interview processes within OB/GYN by both applicants and interviewers. A recent study by Lewkowitz et al of Maternal-Fetal Medicine fellowship applicants suggested that OB/GYN residents are likely to accept more virtual interview offers than in-person interview offers given increased ease and convenience, which may have unintended downstream consequences on the ability of certain candidates to be offered interview opportunities [ 5 ]. Results from our study are in line with these findings, and suggest that it may be prudent to trial a system where applicants are limited in terms of number of accepted interviews to ensure that all qualified applicants are given an opportunity to interview at programs of genuine interest.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, programs needed to rank an additional 1.9 applicants per position, or 7.9 applicants per position compared to 5.9 in 2020, in order to fill in 2021 [ 10 , 11 ]. The “application inflation” has been seen in other specialties including obstetrics, maternal fetal medicine and dermatology [ 7 , 8 , 12 ] and can disadvantage less competitive applicants, ultimately leading to more unfilled positions nationally.…”
Section: Discussionmentioning
confidence: 99%
“…Cost, travel distance, and time away from education are factors favoring virtual interviews, while the desire to interact directly with residents and faculty and to assess potential quality of life in a location are factors in favor of in-person interviews [ 6 ]. Removing the barriers of in-person interviewing allows applicants to interview with more programs [ 3 , 7 ]. But of applicants who completed a virtual interview, 17% still incurred the time and expense to travel to the city to visit informally prior to matching [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results supplement scant existing though expanding knowledge regarding conceptualization of virtual interview processes within OB/GYN by both applicants and interviewers. A recent study by Lewkowitz et al of Maternal Fetal Medicine fellowship applicants suggested that OB/GYN residents are likely to accept more virtual interview offers than in-person interview offers given increased ease and convenience, which may have unintended downstream consequences on the ability of certain candidates to be offered interview opportunities (5). Results from our study are in line with these ndings, and suggest that it may be prudent to trial a system where applicants are limited in terms of number of accepted interviews to ensure that all quali ed applicants are given an opportunity to interview at programs of genuine interest.…”
Section: Discussionmentioning
confidence: 99%